Formation of SMBH seeds in population III star clusters through collisions: the importance of mass loss - Alister Seguel, P. J.; Schleicher, Dominik R. G.; Boekholt, Tjarda; Fellhauer, Michael; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2020)
Runaway collisions in dense clusters may lead to the formation of supermassive black hole (SMBH) seeds, and this process can be further enhanced by accretion, as recent models of SMBH seed formation in Population III star clusters have shown. This may explain the presence of SMBHs already at high redshift, z > 6. However, in this context, mass loss during collisions was not considered and could play an important role for the formation of the SMBH seed. Here, we study the effect of mass loss, due to collisions of protostars, in the formation and evolution of a massive object in a dense primordial cluster. We consider both constant mass-loss fractions as well as analytic models based on the stellar structure of the collision components. Our calculations indicate that mass loss can significantly affect the final mass of the possible SMBH seed. Considering a constant mass loss of 5 per cent for every collision, we can lose between 60-80 per cent of the total mass that is obtained if mass loss were not considered. Using instead analytical prescriptions for mass loss, the mass of the final object is reduced by 15-40 per cent, depending on the accretion model for the cluster we study. Altogether, we obtain masses of the order of $10^4\, M_{\odot }$, which are still massive enough to be SMBH seeds.